An Umbrella Review of Aphasia Intervention descriPtion In Research: the AsPIRE project. Issue 4 (3rd April 2022) - Dipper, L. T.; Franklin, S.; de Aguiar, V.; Baumgaertner, A.; Brady, M.; Best, W.; Bruehl, S.; Denes, G.; Godecke, E.; Gil, M.; Kirmess, C.; Markey, M.; et al.
ABSTRACT: Background: Recent reviews conclude that aphasia intervention is effective. However, replication and implementation require detailed reporting of intervention is and a specification of participant profiles. To date, reviews concentrate more on efficacy than on intervention reporting quality. Aims: The aim of this project is to review the descriptions of aphasia interventions and participants appearing in recent systematic reviews of aphasia intervention effectiveness. The relationship between the quality of these descriptions and the robustness of research design is explored, and the replicability of aphasia interventions is evaluated. Methods and Procedures: The scope of our search was an analysis of the aphasia intervention studies included in the and EBRSR 2018 systematic reviews, and in the RCSLT 2014 literature synthesis. Intervention descriptions published separately from the intervention study (i.e. published online, in clinical tools, or a separate trial protocols) were not included. The criteria for inclusion were that participants had aphasia, the intervention involved language and/or communication, and included the following research designs: Randomised Controlled Trial (RCT), comparison or control, crossover design, case series. Exclusion criteria included non-SLT interventions, studies involving fewer than four participants, conference abstracts, studies not available in English. Studies were evaluated for completeness of intervention description using the TIDieR Checklist. Additionally, we rated the quality of patient and intervention description, with particular reference to replicability. Outcomes and Results: Ninety-three studies were included. Only 14 studies (15%) had >50 participants. Fifty-six studies (60%) did not select participants with a specific aphasia profile, and a further 10 studies only described participants as non-fluent. Across the studies, an average of eight (of 12) TIDieR checklist items were given but information on where, tailoring, modification and fidelity items was rarely available. Studies that evaluated general aphasia intervention approaches tended to use RCT designs, whereas more specific intervention studies were more likely to use case series designs. Conclusions: : Group s tudies were generally under-powered and there was a paucity of research looking at specific aphasia interventions for specific aphasia profiles. There was a trade-off between the robustness of the design and the level of specificity of the intervention described. While the TIDieR framework is a useful guide to information which should be included in an intervention study, it is insufficiently sensitive for assessing replicability. We consider possible solutions to the challenges of making large-scale trials more useful for determining effective aphasia intervention.